Pengaruh Struktur Modal, Profitabilitas, Likuiditas dan Nilai Pasar terhadap Nilai Perusahaan dengan Dividend Sebagai Variabel Moderasi - Ramadhani, Yesa Cahayaning; Maryam, Dewi (Jurnal Manajemen dan Bisnis Indonesia, 2018)
Banks are also industrial institutions whose activities always rely on trust, so they must always maintain the bank's health performance system. Bank health maintenance by maintaining capital adequacy, asset quality, management, achieving sufficient profit and liquidity. The purpose of this research is to test and analyze the effect of the capital structure, profitability, liquidity and market value of corporate value with dividends as a moderating variable.The population in this study are all banking companies listed on the Stock Exchange. The sampling technique was carried out by using purposive sampling technique, which was based on certain criteria so the sample size of 5 samples of each banking industry company - helped distribute dividends during the period 2006 - 2014. The data used were secondary data obtained from the Stock Annual Report Effect. Research hypothesis testing uses multiple linear regression analysis techniques and Residual MRA. The results showed that: 1). Capital structure has no significant effect on the value of the Company, 2). Profitability has a significant effect on Company Value, 3). Liquidity does not have a significant effect on firm value, 4). Market value has no significant effect on the value of the Company, 4). Dividends cannot significantly moderate the Influence of Capital Structure, Profitability, Liquidity and Market Value of the value of the Company.   Keywords: Capital Structure, Profitability, likuidity, Market Value, Value and Dividend  Company